Rituals of Devotion: Unveiling The Intersection of Faith and Haj Practice for Muslims - Hussin, Sabariah (Indo Consultan Energi, 2024)
This paper delves into the intricate relationship between religion and the confluence of faith, spirituality, and ritual within a historical and cultural/symbolic domain. Considering the diversity of religious concepts and the ongoing debate over definitions, the study argues that a rational foundation exists within religious adherents supporting arduous rituals due to historical and religious precedents. Drawing upon the works of Clifford Geertz, Tanya Luhrmann, and Talal Asad, the paper aims to harmonize their varied approaches and formulate a cohesive understanding. The theoretical framework aligns with Geertz's definition of religion as a system of symbols that engenders enduring moods and motivations by crafting conceptions of a general order of existence. This interpretation resonates with the act of pilgrimage, particularly Hajj, where devotees seek communion with God through spiritual sentiments and rigorous rituals. The convergence of Geertz's theory with the works of Luhrmann and Asad forms the basis for comprehending the motivations that propel Muslims onto the well-trodden path of pilgrimage.